2013
DOI: 10.1590/0037-8682-0097-2013
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection and differentiation of mycobacterial species using a multiplex PCR system

Abstract: Introduction:The early diagnosis of mycobacterial infections is a critical step for initiating treatment and curing the patient. Molecular analytical methods have led to considerable improvements in the speed and accuracy of mycobacteria detection. Methods: The purpose of this study was to evaluate a multiplex polymerase chain reaction system using mycobacterial strains as an auxiliary tool in the differential diagnosis of tuberculosis and diseases caused by nontuberculous mycobacteria (NTM) Results: Forty myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
3
3
0
1
Order By: Relevance
“…The identification of M. tuberculosis infections in 63.6 % (35/55) of samples is consistent with other studies that found a higher prevalence of MTB; 67 % [ 26 ], 57.5 % [ 27 ], 78.6 % [ 28 ] and 77 % [ 29 ]. Despite the higher occurrence of MTB, it has been shown elsewhere that the MTB frequency is declining over the years, while the NTM frequency is significantly increased, with prevalence ranging from 9.1 % in 2003 to 31.9 % in 2009 [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…The identification of M. tuberculosis infections in 63.6 % (35/55) of samples is consistent with other studies that found a higher prevalence of MTB; 67 % [ 26 ], 57.5 % [ 27 ], 78.6 % [ 28 ] and 77 % [ 29 ]. Despite the higher occurrence of MTB, it has been shown elsewhere that the MTB frequency is declining over the years, while the NTM frequency is significantly increased, with prevalence ranging from 9.1 % in 2003 to 31.9 % in 2009 [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the natural history of the disease leads to a longer time to diagnosis compared to acute bacterial adenitis. In fact, the persistence of the lymphadenitis is usually the reason for referring to a tertiary care centre, when a median delay of 8-12 weeks is commonly reported in 44% of cases before specialist evaluation [19,46], with a maximum interval between cervical lymphadenitis appearance to definitive treatment reported to be up to one year [41,47]. In the present study the mean interval between symptoms onset and final diagnosis was of 7 Fig.…”
Section: Discussionsupporting
confidence: 42%
“…Esto implica una demora en el inicio del tratamiento que pudo haber afectado el resultado clínico. En ese sentido, la utilización de pruebas rápidas como las de biología molecular (ya disponibles en nuestro medio), puede agilizar el diagnóstico y, por ende, disminuir la mortalidad (23,24). En nuestra serie, el método molecular fue el único estudio que permitió el diagnóstico en 5,3 % de los casos; sin embargo, a la gran mayoría de pacientes no se les hizo este tipo de pruebas, muy probablemente por falta de conocimiento sobre su disponibilidad y por su costo excesivo en el país.…”
Section: Discussionunclassified